2015
DOI: 10.1186/s13633-015-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and pubertal disturbances in optic nerve hypoplasia, from infancy to adolescence

Abstract: BackgroundEndocrinologic abnormalities are a common co-morbidity in patients with optic nerve hypoplasia (ONH), however the impact on puberty is unknown. The purpose of this study was to examine rates of endocrine dysfunction and pubertal disturbances in a pediatric population of ONH.MethodsA retrospective chart review was conducted on a cohort of children with ONH between January 2005 and March 2013. Endocrine dysfunction was determined based on laboratory evidence of hormone deficiency or hormone replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…PHD develops in some patients with ONH, with estimates ranging from 26 to 82%, depending on the sample population [2, 3, 7, 8]. Current studies, although cross-sectional in design, point to an increased risk of developing pituitary hormone deficiencies when structural abnormalities of the pituitary gland are present [9, 10], as well as ophthalmologic factors such as bilateral ONH and blindness [2, 11].…”
Section: Introductionmentioning
confidence: 99%
“…PHD develops in some patients with ONH, with estimates ranging from 26 to 82%, depending on the sample population [2, 3, 7, 8]. Current studies, although cross-sectional in design, point to an increased risk of developing pituitary hormone deficiencies when structural abnormalities of the pituitary gland are present [9, 10], as well as ophthalmologic factors such as bilateral ONH and blindness [2, 11].…”
Section: Introductionmentioning
confidence: 99%
“…However, SOD is heterogeneous and may accompany other brain anomalies and developmental delay [1,2]. Regarding pubertal disturbance, patients with SOD usually show gonadotropin deficiency as a manifestation of hypopituitarism; however, it has been reported that several patients showed central precocious puberty [3]. Here we report a Japanese girl with SOD accompanying Growth Hormone (GH) deficiency, Adrenocorticotropic Hormone (ACTH) deficiency, and central precocious puberty.…”
Section: Discussionmentioning
confidence: 94%
“…This is presumably related to SOD. The most common hormone deficiency is GH alone or in combination with deficiencies in other pituitary hormones [1][2][3][4]. Secondary adrenal insufficiency due to ACTH deficiency has also been reported in SOD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations